1997
DOI: 10.1243/1350650971542273
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lubrication and friction for a complete piston-ring pack with an improved oil availability model: Part 1: Circumferentially uniform film

Abstract: The study of the tribological performance of piston rings plays an important role in piston assembly design. In this study, a comprehensive analysis of piston-ring pack lubrication has been developed. The model employs a flow-continuity algorithm and considers relative ring locations in the piston-ring pack as well as oil accumulation in front of the ring in determining the oil availability. The computer model is able to predict the effect that bore distortion and ring conformability have on piston-ring perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 22 publications
3
75
0
Order By: Relevance
“…Since the initial analytical approach by Furuhama [2], there have been increasing levels of detail in predictive methods, including further salient practical features in the analysis tools. Initially, the improvements in analyses were as the result of a better understanding of regimes of lubrication and improvements in numerical procedures (Dowson et al [3], Ma et al [4], Akalin and Newaz [5], Bolander et al [6], Mishra et al [7,8], D'Agostino and Senatore [9] and Rahmani et al [10]). Good agreement is shown between the predicted and the measured friction presented by Furuhama and Sasaki [11] by a number of contributions such as those of Akalin and Newaz [12] and Mishra et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial analytical approach by Furuhama [2], there have been increasing levels of detail in predictive methods, including further salient practical features in the analysis tools. Initially, the improvements in analyses were as the result of a better understanding of regimes of lubrication and improvements in numerical procedures (Dowson et al [3], Ma et al [4], Akalin and Newaz [5], Bolander et al [6], Mishra et al [7,8], D'Agostino and Senatore [9] and Rahmani et al [10]). Good agreement is shown between the predicted and the measured friction presented by Furuhama and Sasaki [11] by a number of contributions such as those of Akalin and Newaz [12] and Mishra et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that the generated pressures are insufficient to cause any appreciable localised deformation of the contiguous surfaces, thus the lubricant film thickness can be stated as [30][31][32]:…”
Section: Piston Compression Ring Conjunctionmentioning
confidence: 99%
“…From these reports, further studies on various aspects of the ring-liner conjunction have been carried out. Ma et al [16] and Mishra et al [17] examined ring-bore conformability. Ma concluded that bore distortion may reduce the power loss; however oil consumption would increase as a result.…”
Section: Effect Of Compression Ring Elastodynamics Behaviour Upon Blomentioning
confidence: 99%
“…Equation (16) shows the expression for the viscous shear, which varies at each point on the ring: (16) As the viscous shear is a function of film thickness, h, the value of viscous shear varies both circumferentially and axially.…”
Section: Tribological Analysis Of the Top Compression Ringmentioning
confidence: 99%
See 1 more Smart Citation